Analytical study of the high absorption Region of the optical absorption edge of a-Si:H films using the derivative method - Abboo, Abdulla; salih, ,Abeer (Iraqi Journal of Science, 2023)
In this research, optical absorption data (the imaginary part of the dielectric function Ɛ2 as a function of photon energy E) were re-analyzed for three samples of a-Si:H thin films using derivative methods trying to investigate the ambiguity that accompany the interpretation of the optical data of these film in order to obtainm the optical energy gap (Eg) and the factor (r) which in concerned with the density of state distribution near the mobility edge directly without the need for a pre- assumption for the factor r usually followed in traditional methods such as the Tauc plot. The derivative method was used for two choices for the factor q (which in connected with the dependence of the dipole matrix element on the photon energy ) for two choices q=0 and q=2. Results showed that r might take non-integer values . the result for two of the samples, those prepared by Jackson et al and Cody, showed that the derivative plot that adopt q=0 better fits the experimental data, thus Cody’s model might seems closer to the experimental results than the Tauc model. While the third sample the one prepared by Ferlauto et al showed somewhat different behavior such that neither Cody nor Tauc models could be considered a better fit to experimental data for this sample